(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
In recent years, social media has become an integral part of young people’s daily lives. While these platforms provide opportunities for communication, self-expression, and access to information, they also pose potential risks to mental health. This article explores both the positive and negative effects of social media on the psychological well-being of youth and suggests strategies to minimize harmful impacts.